Assessment of school closures in urban areas by simple accessibility measures - Müller, Sven (ERDKUNDE, 2011)
The demographic processes in the eastern regions of Germany have yielded a dramatic decline in student numbers for the time period 1992–2002. This in turn implicates a remarkable school consolidation. In application scenarios, simple measures of the assessment of school closures are needed. In this paper we discuss simple measures of school-accessibility based on public transport travel-times. Moreover, an efficient network flow model to determine the travel-times is presented. Furthermore, a guidance of how a network graph might be constructed is given. As a result of the accessibility analysis, we find that proximate areas are affected by increased travel-times. However, outskirt districts are affected as well. This finding is not obvious, though. The easy-to-understand measures of accessibility presented in this paper might be implemented in the educational planning process. The case study of Dresden is exemplary for other (western) regions in Germany with comparable demographic processes.